MYTH, MEMORY, AND RESILIENCE: REASSESING THE BAKAUA RITUAL IN MINANGKABAU THROUGH STRUCTURALISM AND CULTURAL CONTINUITY - Eka Meigalia; Priscila Fitriasih Limbong; Syahrial Syahrial (Jurnal Gramatika, 2025)
This study explores the resilience of the bakaua ritual in Minangkabau society, focusing on its capacity to endure amid modernization, Islamization, and heritage commodification pressures. While many indigenous rituals have been desacralized or abandoned, bakaua persists as an annual agricultural rite rooted in myth and collective belief. Employing ethnographic fieldwork in Nagari Sijunjung and structuralist analysis of ten foundational myths, this research uncovers the reciprocal relationship between myth and ritual as the key mechanism of persistence. The myths surrounding Syeh Muhsin, a historical cleric mythologized as a sacred figure, provide legitimacy and narrative continuity. In turn, ritual practice actualizes these myths through sacred relics, communal cooperation, and annual recitation, thus embedding them in collective memory. This dynamic interplay between narrative and practice reinforces social cohesion, religious legitimacy, and cultural identity. Findings highlight that Bakaua is not merely a ritual obligation but a cultural strategy for resilience, sustained by collective memory and consciousness. However, external challenges such as tourism-driven commodification and generational shifts pose risks to its sanctity. By linking structuralist insights with theories of collective memory and cultural resilience, this study contributes to broader debates on how rituals adapt and survive in contemporary societies. The research underscores the importance of local agency in heritage preservation, emphasizing that cultural sustainability requires balancing internal values with external pressures. Ultimately, Bakaua exemplifies how myth and ritual co-create resilience, offering a model for understanding intangible heritage persistence globally.